Community Empowerment in Ward Antui Subdistrict Bridge Edge of Bengkalis Regency The Role of Village Heads in Developing Institutions - Darmawan, Jody; Afrianda, Rendi Tri; Putra, Dinda Syufradian (Journal of Governance and Public Affairs, 2024)
This study aims to find out (1) The Role of Lurahs in Fostering Community Empowerment Institutions in the Titian Antui Village Office in Pinggir Bengkalis District, (2) The inhibiting factor of the role of the Lurah in fostering community empowerment institutions in the Titian Antui Village Office in Pinggir Bengkalis District. This research method is descriptive research with a qualitative approach. This descriptive qualitative research is a study that aims to describe. Researchers use source triangulation to check the validity of research data. Data analysis in research II uses three components consisting of data reduction, data presentation, and drawing conclusions. Kelurahan Titian Antui, Pinggir District, Bengkalis Regency, social norms/status have been applied, individuals as organizations in society, individuals in social society. (2) The inhibiting factor of the role of the Lurah in fostering community empowerment institutions in the Titian Antui Village Office in Pinggir Bengkalis District is that it has not been coordinated with the sub -district head and vertical agency in its work area